Study of association of serum bile acid levels with fetomaternal outcomes in cases of intrahepatic cholestasis of pregnancy: a case control study - Jain, Himanshi; Sharma, Manisha; Jain, Rekha; Kumar, Ravindra; Ranjan, Rajiv (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: This study was done to find out the association of serum bile acid level with fetomaternal outcome in patients with intrahepatic cholestasis of pregnancy (IHCP) and to determine the level of bile acids at which immediate intervention will be required to obtain good fetomaternal outcome. Methods: An observational case control study was conducted on 60 women with IHCP as cases and 60 women without IHCP as controls in the department of obstetrics and gynecology at Hindu Rao Hospital and NDMC Medical College from March 2023 to December 2023 and statistical analysis was done using SPSS version 21.0. Quantitative variables were compared using Mann-Whitney test. Qualitative variables were calculated from the receiver operating characteristic curve. The p value of <0.05 was considered statistically significant. Results: The most common symptom of IHCP was itching over whole body seen in 50% cases. Most of the cases (90% cases) were diagnosed with IHCP at 32-37 weeks of gestation. Recurrence was seen in 36.7% cases. 48.3% cases versus 71.7% controls went into spontaneous onset of labour while induction of labour was done in 51.7% cases versus 28.3% controls and augmentation of labour was required in 32.7% cases versus 52.5% controls with statistically significant difference. Preterm delivery was seen in 16.7% cases versus 3.3% controls. 43.3% cases versus 16.7% controls were delivered by cesarean section (p value <0.5). The liquor was meconium stained in 53.3% cases versus 10% controls with a statistically significant difference. 20% cases versus 1.7% controls landed up into PPH at the time of delivery (p value <0.5). There was no statistically significant difference in the fetal outcome, need of NICU admission and birth weight of the babies. The cut-off of 33.7µmol/l bile acid level at the time of diagnosis of IHCP was predictive of MSL, 64.19 µmol/l was the cut off of bile acid for predicting IUD/perinatal death with optimum sensitivity and specificity. 32.85µmol/l was the cut off of bile acid for predicting NICU admissions. A positive correlation was found between the levels of serum bile acid and level of ALT (r value of 0.355 and p value of 0.005), AST levels (r value 0.383 and p value of 0.003), total bilirubin levels (r value 0.355, p value 0.005) and direct bilirubin (r value 0.145, p value 0.271). Conclusions: Significantly higher number of adverse fetomaternal outcomes occurred in the cases of intrahepatic cholestasis of pregnancy as compared to the controls. Increase in the level serum bile acid was associated with increased incidence of adverse fetomaternal outcomes. Serum bile acid levels can be used to predict those adverse fetomaternal outcomes. The adverse fetomaternal outcomes need to be predicted well in time so as to prevent them. Management can be optimized by timely prediction of adverse fetomaternal outcomes with the help of monitoring serum bile acid levels among pregnant women with IHCP.